Tadut : Eksistensi Seni Tutur Besemah Era Modern - Fatrurahman, Afif; Suriana, Sri; Fitriah, Fitriah (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This research is entitled the state of Tadut Oral Speech Art in Besemah Pagaralam in the Modern Era. The subject of this research is [1] How is the state of the art of Tadut oral speech in Besemah Pagaralam now; [2] Is there still a successor to the art of Tadut oral speech in Pagaralam [3] How do the shops today maintain the art of oral speech in Pagaralam. This research uses historical theory and historical studies with a social approach in examining the state of the art of tadut oral speech in Besemah Pagaralam in the modern era. The method used in data collection is done in two ways, namely primary, namely observation, interviews, documentation, and secondary, namely data obtained through books, journals, and articles related to Tadut. Tadut oral literature is a form of oral speech culture chanted by the Besemah community in Pagaralam in ancient times, where the poems in Tadut contain praise, social teachings, parental advice and religious teachings, from this which makes tadut in its history functions as a means of broadcasting Islam in the land of Besemah Pagaralam. From the research that has been known Tadut as it develops has now changed following the times but still survives in an advanced era.